Blazing a Trail: A Public Health Research Agenda in Genomics and Chronic Disease - Colleen M. McBride, PhD (Centers for Disease Control and Prevention, 2005)
Whether and when genomics will lead to public health benefit via reductions in chronic disease burden has provided fodder for debate (1,2). A point of agreement among both proponents and skeptics is that directing genomics research to achieve this end will require integration of knowledge across multiple disciplines and levels of analysis (i.e., biological, behavioral, social, and environmental) (3). Getting started on building these collaborations while the territory is new could temper the disciplinary hegemony that so often presents formidable barriers to transdisciplinary research (4). That said, when it comes to genomics, which has been the bastion of bench scientists and most recently epidemiologists, it may be especially challenging to attract the array of chronic disease researchers with expertise in health education, health psychology, health services delivery, and community-based intervention that will be critical to further this research agenda.